Corneal endothelial dysfunction: Evolving understanding and treatment options. (May 2021) - Price, Marianne O.; Mehta, Jodhbir S.; Jurkunas, Ula V.; Price, Francis W.
Abstract: The cornea is exquisitely designed to protect the eye while transmitting and focusing incoming light. Precise control of corneal hydration by the endothelial cell layer that lines the inner surface of the cornea is required for optimal transparency, and endothelial dysfunction or damage can result in corneal edema and visual impairment. Advances in corneal transplantation now allow selective replacement of dysfunctional corneal endothelium, providing rapid visual rehabilitation. A series of technique improvements have minimized complications and various adaptations allow use even in eyes with complicated anatomy. While selective endothelial keratoplasty sets a very high standard for safety and efficacy, a shortage of donor corneas in many parts of the world restricts access, prompting a search for alternatives. Clinical trials are underway to evaluate the potential for self-recovery after removal of dysfunctional central endothelium in patients with healthy peripheral endothelium. Various approaches to using cultured human corneal endothelial cells are also in clinical trials; these aim to multiply cells from a single donor cornea for use in potentially hundreds of patients. Pre-clinical studies are underway with induced pluripotent stem cells, endothelial stem cell regeneration, gene therapy, anti-sense oligonucleotides, and various biologic/pharmacologic approaches designed to treat, prevent, or retard corneal endothelial dysfunction. The availability of more therapeutic options will hopefully expand access around the world while also allowing treatment to be more precisely tailored to each individual patient. Highlights: The cornea endothelium regulates hydration for optimal transparency and vision. Genetic and environmental factors can cause endothelial dysfunction. Selective endothelial replacement can provide rapid visual rehabilitation. A shortage of human donor corneas restricts access in many parts of the world. Various keratoplasty alternatives are in pre-clinical and clinical trials.